A Brief Review of Drug Delivery System Used in Breast Cancer Therapies - Shah, Niyati; Sapra, Ritu; Suthar, Maitry; Sadhu, Piyushkumar; Mandloi, Nisha; Kumari, Mamta; Talele, Chitrali; Aundhia, Chintan (International Journal of Pharmaceutical Investigation, 2026)
Breast cancer remains a significant global health challenge, necessitating innovative therapeutic approaches to improve patient outcomes. Drug delivery systems have emerged as promising tools to enhance the efficacy and specificity of breast cancer therapies. This comprehensive abstract explores various drug delivery strategies employed in breast cancer treatment, focusing on their mechanisms, advantages, challenges, and recent developments. The abstract begins by outlining the current landscape of breast cancer and the limitations of conventional treatment modalities. It then delves into the diverse classes of drug delivery systems, encompassing nanoparticles-based approaches, targeted delivery systems, stimuli-responsive strategies, and immunotherapy-based systems. The abstract also highlights the significance of combination therapies and addresses the challenges related to drug resistance, toxicity, and biocompatibility. Furthermore, the abstract elucidates recent advances and future perspectives, including personalized drug delivery and the integration of artificial intelligence in optimizing drug delivery systems. Ultimately, this abstract aims to provide a comprehensive and insightful overview of drug delivery systems used in breast cancer therapies, shedding light on the potential of these technologies to revolutionize breast cancer treatment.
Keywords: Personalised Drug Delivery; Nanoparticle Based Approach; Breast Cancer; Targeted Drug Delivery.